2003
DOI: 10.1038/sj.embor.embor804
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of PDZD2 generates a secreted peptide containing two PDZ domains

Abstract: scientific report 412PDZD2 (PDZ-domain-containing 2; also known as PAPIN, AIPC and PIN1) is a ubiquitously expressed multi-PDZ-domain protein. We have shown that PDZD2, which shows extensive homology to prointerleukin-16 (pro-IL-16), is localized mainly to the endoplasmic reticulum (ER). Pro-IL-16 is cleaved in a caspase-3-dependent mechanism to generate the secreted cytokine IL-16. The abundant expression of PDZD2 in the ER, and its sequence similarity to pro-IL-16, suggests that similar post-translational pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…Over a region of 215 amino acids, there is 39.5% identity and 58.1% similarity [31]. Consistent with this sequence similarity and the abundant expression of PDZD2 in the endoplasmic reticulum (ER) [31], we demonstrated that PDZD2 is proteolytically cleaved by caspase-3 [31,35] to generate the secreted form of PDZD2 (sPDZD2, Fig. 1), analogous to the processing of pro-IL-16 to generate the secreted cytokine IL-16 [36] (Fig.…”
Section: Pdzd2 Is Subjected To Proteolytic Cleavage To Generate Spdzdsupporting
confidence: 73%
See 3 more Smart Citations
“…Over a region of 215 amino acids, there is 39.5% identity and 58.1% similarity [31]. Consistent with this sequence similarity and the abundant expression of PDZD2 in the endoplasmic reticulum (ER) [31], we demonstrated that PDZD2 is proteolytically cleaved by caspase-3 [31,35] to generate the secreted form of PDZD2 (sPDZD2, Fig. 1), analogous to the processing of pro-IL-16 to generate the secreted cytokine IL-16 [36] (Fig.…”
Section: Pdzd2 Is Subjected To Proteolytic Cleavage To Generate Spdzdsupporting
confidence: 73%
“…This finding indicates that the NLS-like sequence is functional. The nuclear localization of PDZD2 [31] and the identification of a functional NLS suggest a nuclear function of PDZD2, consistent with its interaction with E2A proteins. Multi-PDZ proteins function by mediating the formation of multi-molecular complexes through their multiple PDZ domains.…”
Section: Pdzd2 Has a Functional Nlssupporting
confidence: 55%
See 2 more Smart Citations
“…In vitro treatment with recombinant sPDZD2 induces p53 up-regulation in human prostate cancer (DU-145), breast adenocarcinoma (MCF-7), and liver cancer (Hep-G2) cell lines, 64 and such altered p53 activity may inhibit epithelial-mesenchymal transition. 65 More important, though, PDZD2 is expressed in the nucleus and also secreted after cleavage, 66 suggesting a potentially complex role in these processes.…”
Section: Discussionmentioning
confidence: 99%